A new indicator of the effectiveness of urban green infrastructure based on ecosystem services assessment - de Manuel, B. Fernández; Méndez-Fernández, L.; Peña, L.; Ametzaga-Arregi, I. (Basic and applied ecology, 2021)
•The urban green infrastructure has to provide multiple benefits to citizens.•Tools that assess the effectiveness of the urban green infrastructure are needed.•We quantified the ES delivered by each urban green and blue space in the city.•The index of mismatches between supply and demand of ES (MbSDES) is a useful tool.•The spatially explicitly index identified deficit areas to urban planners and managers. The contribution of urban green infrastructure (UGI) to human well-being has been demonstrated in several studies. A common method to evaluate such contributions is to measure the ecosystem services (ES) provided by the vegetation or water bodies present in urban green and blue spaces (UGBS) that constitute the UGI. The efficiency and spatial distribution of diverse types of UGBS in the provision of various ES could be considered by urban planners or managers to define specific objectives in future planning processes. In this context, we propose a methodological approach to develop an effective UGI based on an index of mismatches between supply and demand of ES (MbSDES) that addresses the mismatches between supply and demand for three ES (run-off retention, air purification, and cooling) provided by different UGBS in the city of Bilbao (Basque Country, North Spain). ES supply and demand for the three ES were at the urban neighbourhood level. The results indicate that there was a clear mismatch between ES supply and demand in the study area with 35% of the neighbourhood showing negative values for the MbSDES, which indicated that the actual UGBS do not satisfy the demand for ES. Hence, those areas with ES supply deficits should be a priority when planning new green areas (parks, tree lines, urban gardens) within the municipality. This challenge could be addressed by selecting the type of UGBS structure that is planned and improving the net efficiency of the UGI.